2019
DOI: 10.1016/j.joi.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The balance of knowledge flows

Abstract: In analogy to the technology balance of payments, in this paper we propose a possible way to set up a "balance of knowledge flows" (BKF), recording world flows of knowledge within the scientific community. Adopting a pure bibliometric approach, the "knowledge" traced in the BKF is that produced and exchanged by the scientific community by means of publications and relevant citations. A description of the theoretical foundation of such a tool is presented together with its empirical testing over the scientific … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Many scholars have investigated the phenomenon of knowledge diffusion, also referred as "knowledge spillovers" and "knowledge flows" (Jaffe, Trajtenberg, & Henderson, 1993;Hicks, Breitzman, Olivastro & Hamilton, 2001;Tijssen, 2001;Maurseth & Verspagen, 2002;Thompson & Fox-Kean, 2005;Sonn & Storper, 2008;Belenzon & Schankerman, 2013;Jaffe & De Rassenfosse, 2017;Abramo, D'Angelo, & Carloni, 2019). A remarkable work of classification of the large amount of studies on the subject was carried out by Cerver-Romero, Ferreira and Fernandes (2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many scholars have investigated the phenomenon of knowledge diffusion, also referred as "knowledge spillovers" and "knowledge flows" (Jaffe, Trajtenberg, & Henderson, 1993;Hicks, Breitzman, Olivastro & Hamilton, 2001;Tijssen, 2001;Maurseth & Verspagen, 2002;Thompson & Fox-Kean, 2005;Sonn & Storper, 2008;Belenzon & Schankerman, 2013;Jaffe & De Rassenfosse, 2017;Abramo, D'Angelo, & Carloni, 2019). A remarkable work of classification of the large amount of studies on the subject was carried out by Cerver-Romero, Ferreira and Fernandes (2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of such studies show that geographical distance is quite significant on the national level, and affects the knowledge flow on the continental level as well, but becomes insignificant on the international, intercontinental level. The role of geographic closeness in knowledge flow can be attributed to the importance of direct personal interactions and social effects, like connections with mentors, the effect of schools in the research field, and on the domestic level of biases in citation practices favouring domestic research [88,101]. Other studies have reported similar results, showing that citation links decrease with increasing distance [83,86].…”
Section: Disciplinary Structure At Country Levelmentioning
confidence: 84%
“…The knowledge flows occur not only between different disciplines; there are significant and important knowledge flows between sciences and areas where their knowledge is consumed. Consequently, researchers of Science of Science have explored such dynamics of knowledge production and consumption from the perspective of the exchange balance of scientific knowledge [88] and also as "food webs" of knowledge; as dynamic networked systems [89].…”
Section: Interdisciplinarity and Knowledge Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abramo and D'Angelo (2018 tracked international spillovers of Italian knowledge production, in over 200 fields, by analyzing publication citations. Abramo, D'Angelo, and Carloni (2019) conceptualized the diffusion of knowledge between countries in terms of a "balance of knowledge flows" (BKF). Several studies investigated, among others, the role of geographic, cognitive and social proximity in knowledge diffusion (Jaffe, Trajtenberg, & Henderson, 1993;Hicks, Breitzman, Olivastro & Hamilton, 2001;Tijssen, 2001;Maurseth & Verspagen, 2002;Ahlgren, Persson, & Tijssen, 2013;Head, Li, & Minondo, 2018;Wuestman, Hoekman, & Frenken, 2019, Abramo, D'Angelo, & Di Costa, 2020a.…”
Section: Introductionmentioning
confidence: 99%